7p+4-2p+1=8p+2

Simple and best practice solution for 7p+4-2p+1=8p+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7p+4-2p+1=8p+2 equation:


Simplifying
7p + 4 + -2p + 1 = 8p + 2

Reorder the terms:
4 + 1 + 7p + -2p = 8p + 2

Combine like terms: 4 + 1 = 5
5 + 7p + -2p = 8p + 2

Combine like terms: 7p + -2p = 5p
5 + 5p = 8p + 2

Reorder the terms:
5 + 5p = 2 + 8p

Solving
5 + 5p = 2 + 8p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-8p' to each side of the equation.
5 + 5p + -8p = 2 + 8p + -8p

Combine like terms: 5p + -8p = -3p
5 + -3p = 2 + 8p + -8p

Combine like terms: 8p + -8p = 0
5 + -3p = 2 + 0
5 + -3p = 2

Add '-5' to each side of the equation.
5 + -5 + -3p = 2 + -5

Combine like terms: 5 + -5 = 0
0 + -3p = 2 + -5
-3p = 2 + -5

Combine like terms: 2 + -5 = -3
-3p = -3

Divide each side by '-3'.
p = 1

Simplifying
p = 1

See similar equations:

| 100=x+(x*4)+(x*4) | | (x+3)+(x+8)=21 | | 5^7x-9=1/125 | | ln(8x+1)=6 | | 92x=36 | | 6-3x-5x-x=10 | | 2ef+3ef= | | 5x+(7x+2)+(7x+6)= | | 2m^2=-4m+6m | | 7q-4q+8= | | 3b^4+18b^3+27b^2= | | log(2x-4)=-0.7 | | 2x+5=-2x-8-x | | -40=8(x-3)-3/2(6x-16 | | .16x+1500=x | | (X)2+(Y-1)2=81 | | 0=16t^2+96t-140 | | 5k^2+20k+100=0 | | 5k^2+20k+100=100 | | (x-5)-(x-12)= | | (t/2-20)/4=4 | | 5*7x^2y=175 | | 21/15=3x-2/5 | | 12/3x=36/63 | | 5m(4m+11)= | | Y=(8-x)^1/2 | | 4x=x+180 | | 13.2x+x^2-1246=0 | | 34x-9x+12=20+3x | | 4t-6h+8t-12h+4= | | 1/2(-0.86) | | 35=-29+(n-1)(-7) |

Equations solver categories